Análise do desenvolvimento no estado do Tocantins na perspectiva da imprensa - Lima, Neuracy Viana Cruz (Universidade Federal do Tocantins, 2023)
This study analyzed the development process in the State of Tocantins from the perspective of the press. The newest Brazilian federative unit was created on October 5, 1988, after dismemberment with the State of Goiás. Before, it belonged to a region considered forgotten andbackward, a reality that began to change with the territorial division. In this context, the press, which in its practice works to disseminate facts of collective interest and promotes debates on various subjects, made public facts referring to the region's political and administrative autonomy, as well as its economic and social growth. Thus, to find out how local development was reported, the topics covered, the predominant journalistic genres and who was given the power of representation to express themselves on the subject researched during the first 30 yearsafter the creation of the State (1988- 2018) analysis of framing, classification of journalistic genres and of sources and voices present in selected texts of Jornal do Tocantins, a printed vehicle, with 42 years of activity in the region, were carried out. A total of 525 texts were analyzed, distributed in 38 tables and six thematic axes, having been identified two journalistic genres and 39 categories of sources and voices. The results achieved reveal a comprehensive coverage of development, having addressed several aspects about the subject, however, with great predominance in the economic area. Due to the diversity of themes identified, it can be saidthat coverage was heterogeneous, and in the three decades surveyed, it was found that the theme of development was frequently present on the press agenda. The texts published are predominantly of an informative genre and of a more regional and local nature, and the sources and voices of the state government were the ones that had the most space in the newspaper to pronounce on the subject under study.